Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations 24 HEALTH AND CLEANLINESS [Image with caption: A SLICE THROUGH NORMAL HEALTHY SKIN] 177/5/8/3